Parabolic trough efficiency gain through use of a cavity absorber with a hot mirror. (15th March 2019) - Mohamad, Khaled; Ferrer, P.
Highlights: Introducing a novel design of a parabolic trough collector receiver unit, using cavity and hot mirror coating. The design is a strong candidate to reduce the dominant radiant energy losses and increasing absorber efficiency. The working fluid temperature and the efficiency exceed existing alternatives. Abstract: The solar parabolic trough collector is amongst the most mature solar technologies and has become more cost effective in recent years. In this paper, a novel design for the receiver unit is presented which aims to decrease the radiant energy losses while raising the temperature of the working fluid, when compared to conventional systems. The design incorporates the application of different optically active layers in conjunction with a cavity absorber. The cavity geometry and a hot mirror coating at the aperture enable heightened retention of thermal radiation of the receiver. The additional, novel aspects of the background theory of the design is presented and implemented in a simulation. The simulation results for receiver temperature profiles, heat transfer fluid temperature, and efficiencies are shown. It is seen that our proposal has advantages in terms of thermal behavior over conventional designs in that it can exceed the heat transfer fluid temperature and the efficiency of existing alternatives.